Cretonthophilus tuberculatus, a remarkable new genus and species of hister beetle (Coleoptera: Histeridae) from Cretaceous Burmese amber - Caterino, Michael S.; Wolf-Schwenninger, Karin; Bechly, Günter (Zootaxa, 2015)
The early history of the beetle family Histeridae is still very obscure. In part this results from difficulty resolving phylogenetic relationships at deeper levels (Caterino & Vogler, 2002; McKenna et al., 2015a). But it is also partly a result of a sparse and poorly documented fossil record (Chatzimanolis et al., 2006). Here we describe a new genus and species of fossil histerid from Burmese amber ( 99 mya), which helps to address both of these problems.